A ideia de lúdico na matemática de Malba Tahan - Garcia, Elifaz de Souza Frias (2024)
Júlio César de Mello e Souza (1895 - 1974) was first trained as a civil engineer at the National School of Engineering. He never practiced. Coming from an educational family, his passion was teaching. As a writer, he created the heteronym Malba Tahan. He wrote around 120 books (including short stories and books on mathematics and mathematics education). His book "The Man Who Calculated" is now in its 100th edition. He also gave several lectures and articles aimed at teachers. During his lessons, in order to get his students' attention, he used jokes, imitations of animals and games. He used the concept known as the ludic method. In this dissertation, we will analyze aspects of the idea of play developed by Prof. Júlio Cesar de Mello e Souza and some of his relationships with the concept of play today, as well as in the past